Tingkat kematangan gonad ikan Lais (Ompok hypopthalmus) yang tertangkap di rawa banjiran sungai Rungan Kalimantan Tengah - Infa Minggawati; - Lukas (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
The purpose of this study was to determine the catfish gonad maturity level caught in a flooding swamp area of Rungan River in Palangka Raya, Central Kalimantan. The experiment was conducted in October 2013 to April 2014. The fish specimens were analyzed to determine the level of maturity of the gonads. Moreover, water quality was measured. Total fish caught was 353 fishes, with a percentage of 61% males and 39% females, and the total length of fish ranging from 12-29 cm and weight between 10-250 grams. Types of the catfish food were shrimp, insects and fish juvenile. Spawning peaks in gonad maturity level IV were in December 2013 and January 2014, with water depth from 4.03 to 6.5 meters, the average water temperature 26.9oC, pH 4.6 DO 3.4 mg/L and 27.6 cm water transparency. Key words : Ompok hypopthalmus, Catfish, gonads maturity level, flooding swamp